Tissue factor-bearing microparticles and cancer-associated thrombosis (Hematology Meeting Reports, 2009)
Microparticles were first described in normal blood as platelet dust.1 Sims carefully studied the generation of platelet microparticles during platelet activation by complement.2 These platelet microparticles bind to Factor Va and support prothrombinase activity3 as well as bind to Factor VIII.4 Since these reports, hundreds of studies have monitored microparticles, primarily using flow cytometry and light scattering, and correlated microparticle antigen expression within diverse groups of diseases. However, microparticles have been subjected to limited chemical analysis, including their lipid and protein content.